A multidimensional investigation of the relationship between skin-mediated somatosensory signals, emotion regulation and behavior problems in autistic children - Riquelme, Inmaculada; Hatem, Samar M.; Sabater-Gárriz, Álvaro; Montoya, Pedro (Frontiers in Neuroscience, 2023)
Introduction Autistic children may have abnormal sensory perception, emotion dysregulation and behavior problems. The aim of this cross-sectional study was to explore the relationship between skin-mediated somatosensory signals and emotion/behavior difficulties in autistic children and adolescents, in comparison typically developing peers (TDP). Methods Thirty-eight autistic children and adolescents and 34 TDP completed a multidimensional assessment consisting of the measurement of somatosensory thresholds of touch, pain and temperature, a task on emotion knowledge and parent-reported questionnaires on sensory reactivity, emotion regulation and behavior. Results Autistic children had higher pain sensitivity, less sensory reactive behaviors and more behavior problems than their TDP. In contrast to TDP, several somatosensory thresholds of autistic children correlated with emotion regulation and behavior problems. Discussion Sensory dysfunction may affect the development of emotional processing and behavior in autistic children and adolescents. This knowledge can lay the foundation for future studies on co-occurring alterations in corresponding neural networks and for the implementation of early interventions, including sensory rehabilitation therapy, for promoting regulated behaviors in autistic children and adolescents.